CONTEXTUAL TEACHING AND LEARNING IN IMPROVING STUDENTS’ LANGUAGE ACHIEVEMENT IN JUNIOR SECONDARY ENGLISH CLASSROOMS - Tina Sheba Cornelia Sitompul; Dewi Afriany Susanti (SENSEI RESEARCH CENTER, 2024)
English learning is often felt difficult by the students because the material is not related to their daily life. Contextual Teaching and Learning is one of the approaches that can be used to solve this problem. This study discusses the implementation of Contextual Teaching and Learning in improving students' language achievement. The study used a mixed-method design with an experimental class and a control class. The data were collected through a language achievement test, observation, interviews, and reflective journals. The result shows that the experimental class is better than the control class and the students are more active and more confident during the lesson. Therefore, teachers are suggested to apply Contextual Teaching and Learning in English classrooms.